Characterisation of IncA/C2 plasmids carrying an In416-like integron with the blaVIM-19 gene from Klebsiella pneumoniae ST383 of Greek origin - Papagiannitsis, Costas C; Dolejska, Monika; Izdebski, Radosław; Giakkoupi, Panagiota; Skálová, Anna; Chudějová, Kateřina; Dobiasova, Hana; Vatopoulos, Alkiviadis C; Derde, Lennie P G; Bonten, Marc J M; Gniadkowski, Marek; Hrabák, Jaroslav (International journal of antimicrobial agents, 2016)
The complete nucleotide sequences of three multidrug resistance (MDR) IncA/C-like plasmids from Enterobacteriaceae isolates carrying the VIM-type carbapenemase-encoding integrons In4863 (blaVIM-19-aacA7-dfrA1-ΔaadA1-smr2) or In4873 (blaVIM-1-aacA7-dfrA1-ΔaadA1-smr2) were determined, which are the first In416-like elements identified in Greece. Plasmids pKP-Gr642 and pKP-Gr8143 were from Klebsiella pneumoniae ST383 isolates, whereas plasmid pEcl-Gr4873 was from an Enterobacter cloacae ST88 isolate. Sequencing showed that pKP-Gr642 (162787bp) and pKP-Gr8143 (154395bp) consisted of the type 1 IncA/C2 conserved backbone, the blaCMY-2-like gene-containing region, and the ARI-B (with the sul2 gene) and ARI-A (with a class 1 integron) resistance islands, like the plasmid pUMNK88_161 from the USA. The third plasmid, pEcl-Gr4873 (153958bp), exhibited extensive similarity with the type 2 IncA/C2 plasmid pR55 from France. pEcl-Gr4873 carried only one resistance island of a hybrid transposon structure inserted in a different location to ARI-A in type 1 A/C2 plasmids. In all three plasmids, the In416-like integrons In4863 or In4873 were identified within non-identical class II transposon structures. All three In416-like-carrying regions presented significant similarities with the MDR region of the IncA/C2 plasmid pCC416 from Italy, carrying the prototype In416 integron (blaVIM-4-aacA7-dfrA1-ΔaadA1-smr2). These findings provided the basis for speculations regarding the evolution of IncA/C2 plasmids with In416-like integrons, and confirmed the rapid evolution of some IncA/C2 plasmid lineages. Considering the broad host range of IncA/C2 molecules, it seems that pKP-Gr642, pKP-Gr8143 and pEcl-Gr4873 plasmids might support the diffusion of In416-like integrons among Enterobacteriaceae.
Keywords: sekvenční homologie; beta-laktamasy; Greece; integrony; lidé; Molecular Sequence Data; beta-Lactamases; Sequence Homology; molekulární sekvence - údaje; plazmidy; pořadí genů; Sequence Analysis, DNA; Enterobacteriaceae Infections; Plasmids; sekvenční analýza DNA; Integrons; enterobakteriální infekce; Klebsiella pneumoniae; Gene Order; Řecko; Enterobacter cloacae; Humans